Biodegradable transformation through environmental treatment withminerals un the Huacachina kagoon, Ica-Peru: A pilot study - Argota Pérez, George (2024)
The objective of the study was to analyze the biodegradable transformation by environmental treatment with minerals in the Huacachina lagoon, Ica-Peru.Between May and August 2023, two sampling points were selected probabilisticallyat shore level and with a distance of approximately 80 m for the measurement of BOD5,20 and COD before and after treating the available water by means of a mineral system with two layers for the removal of BOD5,20 and COD: 1st) silicate sand, and 2nd) granulometric activated carbon. The percentage of removal for the parameters were: BOD5,20 (point 1 = 22.31%; point 2 = 23.97%) and COD (point 1 = 23.0%; point 2 = 20.28%). The transformation coefficient indicated that the waters are biodegradable (point 1 = 0.44; point 2 = 0.5 / biodegradablecondition = 0.2-0.7). Although the BOD5,20 and COD values decreased withthe mineral treatment system, the final concentration indicated non-compliance with the regulatory level. It is concluded that the biodegradable transformation through environmental treatment with minerals in the Huacachina lagoon decreased the organic matter content, although it was not sufficient to consider the quality of the water removed as adequate.